Thermal boundary layer over a vertical plate in porous medium with a convective surface boundary condition - Suhaimi, Ehsan; Rosali, Haliza; Md Ali, Fadzilah (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2024)
This study aims to investigate the thermal boundary layer over a vertical plate in porous medium with a convective surface boundary condition. The governing systems of partial differential equations subject to the boundary conditions are transformed into the system of ordinary differential equations by employing the similarity transformation. The bvp4c method in Matlab software is used to numerically solve the equations. With the use of graphical and tabular data, the velocity and temperature profiles for various parameter values is obtained, analyzed, and discussed. The effects of the governing parameters involved including permeability parameter K and the buoyancy parameter λ are examined and discussed. The local Nusselt number and skin friction coefficient increase as the permeability parameter's K value rises. The results suggest that dual solutions for opposing flow and the solution is unique for assisting flow. The results also shown that by increasing K, the permeability parameter, will increase the range of solutions. Lastly, the permeability parameter, K, has the consequence of expanding the range values of buoyancy parameter, λ for which solutions are discovered.